Integrated sensing and communication in reconfigurable intelligent surface systems: status, design and outlook - Xiaoling HU; Zhouyuan YU; Xiaowei QIAN; Mugen PENG (Dianxin kexue)
Integrated sensing and communication (ISAC) is the dominant trend of the sixth generation mobile communication networks (6G).The introduction of ISAC into the reconfigurable intelligent surface (RIS) system can expand the system coverage, improve both communication and sensing performances, and reduce the hardware cost as well as the power consumption of the system.On the basis of outlining and analyzing the research status of ISAC in RIS systems, two non-orthogonal ISAC methods were proposed to support concurrent communication and sensing for blind-zone users on non-orthogonal time-frequency resources.Finally, the technical challenges and future development of ISAC in RIS systems were discussed.